Eurosceptycyzm znad Wełtawy. Inspiracja brytyjska czy oryginalny wariant czeskich konserwatystów? - LESZCZYŃSKI, Paweł (Przegląd Politologiczny, 2018)
The aim of this paper is to reveal the connections between the British version of Euroskepticism (as one variety of this political and intellectual phenomenon) and its Czech variant, personified by the present President of the Czech Republic – Vaclav Klaus. The paper discusses the fundamental elements of the Euroskeptical outlook that are sometimes presented to public opinion in EU states as ‘Eurorealism.’ The British variety is presented alongside the most important elements of the same concept in France and Denmark. Although Czech Europskepticism refers to numerous significant structural elements of its British predecessor, it has a number of original features. Among others, they result from the geopolitical conditions of Central Europe. The author analyzes the statements of the present Czech president (who once described himself as a Thatcherist) to show his essential influence on the shape of Euroskeptical attitudes on the Vltava. The author also presents the most important foreign policy documents of the former political circles of Vaclav Klaus, i.e. the Civic Democratic Party (ODS), with their Europskeptical overtones. The paper concludes with the author’s observations concerning the similarities and discrepancies between British and Czech attitudes.